2016
DOI: 10.1186/s12938-016-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

The configuration of plantar pressure sensing cells for wearable measurement of COP coordinates

Abstract: BackgroundWearable measurement of center of pressure (COP) coordinates is the key of obtaining the measurement of natural gait. Plantar pressure insole is the right sensing unit for plantar pressure monitoring for long-term outdoor measurements and the control of walking assisting exoskeleton robot. It’s necessary to study the configuration of pressure sensing cells.MethodsThis study explored the sensing cell configuration for the plantar pressure insole. The data of plantar pressure of walking is collected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…By considering that we adopted larger size sensors, our results find agreement with Stöggl and Martiner [16], who reported an underestimate ranging between 35.1% (RMSE%) and 76.4% (RMSE%) on GRF with a Moticon device characterized by 13 sensors. It should be mentioned that Figures 2-8 showed that the results of the simulated layouts were mainly affected in terms of the amount of peak of pressure that was underestimated rather than its spatial location on the insole, in agreement with Wang 2016 [50], who compared the influence of different layouts, sizes, and number of pressure-sensing cells on COP coordinates' estimation. Their results indicated that reliable COP estimation could be obtained with seven pressure-sensing cells of 2.0-2.5 cm, which represented the best compromise between simplifying the wearable system and obtaining precise information.…”
Section: Weight Liftingsupporting
confidence: 83%
See 1 more Smart Citation
“…By considering that we adopted larger size sensors, our results find agreement with Stöggl and Martiner [16], who reported an underestimate ranging between 35.1% (RMSE%) and 76.4% (RMSE%) on GRF with a Moticon device characterized by 13 sensors. It should be mentioned that Figures 2-8 showed that the results of the simulated layouts were mainly affected in terms of the amount of peak of pressure that was underestimated rather than its spatial location on the insole, in agreement with Wang 2016 [50], who compared the influence of different layouts, sizes, and number of pressure-sensing cells on COP coordinates' estimation. Their results indicated that reliable COP estimation could be obtained with seven pressure-sensing cells of 2.0-2.5 cm, which represented the best compromise between simplifying the wearable system and obtaining precise information.…”
Section: Weight Liftingsupporting
confidence: 83%
“…State-of-the-art also reported solutions with a reduced number of sensors with larger size such as Wang et al, 2016 [ 50 ] and Shu et al, 2010 [ 22 ], where the entire foot sole was divided into 6 or 7 sensors, respectively, with 4 or 3 pressure-sensing cells in the metatarsal region, 1 pressure-sensing cell or none in the midfoot, and 3 pressure-sensing cells in the heel region. By considering that we adopted larger size sensors, our results find agreement with Stöggl and Martiner [ 16 ], who reported an underestimate ranging between 35.1% (RMSE%) and 76.4% (RMSE%) on GRF with a Moticon device characterized by 13 sensors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be surmised that a minimum number of sensors may be required to accurately measure COP path width. This supposition is supported by the work of Wang et al, 17 who found that an increase in the number of sensors led to a more accurate measurement of COP. Researchers should be aware of this limitation when using smaller sized pressure measuring insoles, as they may lack the number of sensors required to produce accurate COP results.…”
Section: Discussionmentioning
confidence: 71%
“…It was found that both methods were successful in determining COP. Wang et al 17 used pressure-measuring insoles, with various numbers of sensors, to examine the COP of 10 healthy adults. It was found that an increase in the number of sensing cells lead to a better estimation of COP.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of pressure insoles for measuring widths of the COP can be affected by sensor size, sensor arrangement, the number of sensors, individual sensor accuracy and repeatability, differences in sampling rate between the systems, and/or measurement context. Wang et al 37 observed that an increase in the number of sensors across the width of an insole resulted in a more accurate measurement of the width of trajectories of the COP. Therefore, a smaller number of sensors in the ML direction compared to the AP direction may be a contributing factor as well as because differences between the systems may be amplified due to the short-measured distance.…”
Section: Discussionmentioning
confidence: 99%